Assessing and reducing vulnerability to climate change: Moving from theory to practical decision-support. (December 2016) - Johnson, Johanna E.; Welch, David J.; Maynard, Jeffrey A.; Bell, Johann D.; Pecl, Gretta; Robins, Julie; Saunders, Thor
Abstract: As climate change continues to impact socio-ecological systems, tools that assist conservation managers to understand vulnerability and target adaptations are essential. Quantitative assessments of vulnerability are rare because available frameworks are complex and lack guidance for dealing with data limitations and integrating across scales and disciplines. This paper describes a semi-quantitative method for assessing vulnerability to climate change that integrates socio-ecological factors to address management objectives and support decision-making. The method applies a framework first adopted by the Intergovernmental Panel on Climate Change and uses a structured 10-step process. The scores for each framework element are normalized and multiplied to produce a vulnerability score and then the assessed components are ranked from high to low vulnerability. Sensitivity analyses determine which indicators most influence the analysis and the resultant decision-making process so data quality for these indicators can be reviewed to increase robustness. Prioritisation of components for conservation considers other economic, social and cultural values with vulnerability rankings to target actions that reduce vulnerability to climate change by decreasing exposure or sensitivity and/or increasing adaptive capacity. This framework provides practical decision-support and has been applied to marine ecosystems and fisheries, with two case applications provided as examples: (1) food security in Pacific Island nations under climate-driven fish declines, and (2) fisheries in the Gulf of Carpentaria, northern Australia. The step-wise process outlined here is broadly applicable and can be undertaken with minimal resources using existing data, thereby having great potential to inform adaptive natural resource management in diverse locations. Highlights: Quantitative assessments of climate change vulnerability are rare and complex. This semi-quantitative assessment integrates socio-ecological factors to deliver targeted results. The SQA method can be tailored to any context (spatial or temporal) and is repeatable. The method uses indicators and an equation to calculate and rank vulnerability and prioritise management. Results lead to a transparent process for evaluating trade-offs between short-term priorities and longer-term adaptations.